A Game Experience Scoring Approach on Digital Educational Games and Cognitive Styles Behaviour - Dinna N. Mohd Nizam; Zaidatol Haslinda Abdullah Sani; Aslina Baharum; Siti Hasnah Tanalol; Laura Penny Jack (2020)
Assessing game experience on Digital Educational Games (DEGs) can enhance knowledge on users behaviour and experiences. The growth and popularity for DEGs among the young continues to evolve therefore further studies remains required. This study investigated how game experiences were related to children’s cognitive styles (i.e., focused attention and interaction strategies) on DEGs. In this study, a game experience scoring approach was used to examine the cognitive styles. Preliminary results presented that the Working Area of the DEG influenced a child's game experience and the Distractor was less seen by children during the interactive sorting activity. Focus attention on the Working Area and Banner works closely together (p<.05) indicating that children revisit items for confirmations. As for game experience on interaction strategies, an enjoyable game experience can be achieved when a child practice structured gameplay that develops into attention and engagement. Overall this study expands the knowledge of objects in game design and human behaviour for young children in DEGs.